ANALISIS HARGA TANDAN BUAH SEGAR KELAPA SAWIT DI KABUPATEN PASANGKAYU - Hasriani Hasriani; Buyung Romadhoni; Andi Mappatompo (COMPETITIVENESS, 2021)
This study aimed to determine the difference in the price of palm tree fresh fruit bunch in Pasangkayu Regency and to find out why the various traders’ behavior in giving prices to farmers. This study used qualitative research. The type of this research approach was descriptive. To determine the informants in this study was throung the snowball sampling technique. Snowball technique was a sampling method in which informants are obtained through a rolling process from one informant to another. The number of informants in this study were 8. The results showed that differences in ownership of ISPO and RSPO certificates for each palm oil company affects the price policy offered by each company. The difference in prices received by farmers was also influenced by the behavior of collectors in determining prices, each of them incurs a different amount, the costs are transportation, wage of workers, distance, quality of fruit, and operational costs as well as the amount of profit that collectors want to get. Keywords: Price, Fresh Fruit Bunches.